THE ESSENCE OF DISASTER EDUCATION AT THE JUNIOR HIGH SCHOOLS IN LANDSLIDE DISASTER PRONE-AREA, TAWANGMANGU, INDONESIA - Tri Indyastuti; Safira Alfanisa; Mifta Widya Ningrum; Rehan Permana Agung; Alif Akbar Kurniansyah; Yunus Aris WIbowo (Universitas Sebelas Maret (UNS), 2023)
Disaster education is an effort that is expected to increase preparedness and reduce the risk posed by a natural disaster. One area that has a high risk of landslides is the Karanganyar Regency. This study aims to analyze the urgency of disaster education and the role of Junior High schools in supporting disaster education in landslide-prone areas, Tawangmangu Subdistrict. The approach used in this study is a quantitative approach using primary data obtained through questionnaires and interviews. The sampling technique in this study used a purposive sampling technique where the research samples were Social Science subject teachers at State Junior High School 01 of Tawangmangu, Junior High School of Amal Mulya Tawangmangu, and Junior High School of Penda Tawangmangu. The analytical technique used was descriptive statistical analysis. Based on the results, it can be concluded that schools were aware of the essence of disaster education. The Junior High Schools in Tawangmangu Subdistrict supports the urgency of disaster education, by realizing its role through several activities in schools that can increase the preparedness, capacity, and knowledge of students against potential hazards around their houses. With the existence of disaster education in schools, it is expected to be able to increase the capacity of students to reduce the risk posed by a landslide disaster.